Anti-Streptococcal activity of Brazilian Amazon Rain Forest plant extracts presents potential for preventive strategies against dental caries - Juliana Paola Corrêa da SILVA; Adriana Lígia de CASTILHO; Cíntia Helena Couri SARACENI; Ingrit Elida Collantes DÍAZ; Mateus Luís Barradas PACIÊNCIA; Ivana Barbosa SUFFREDINI (University of São Paulo, 2014)
Caries is a global public health problem, whose control requires the introduction of low-cost treatments, such as strong prevention strategies, minimally invasive techniques and chemical prevention agents. Nature plays an important role as a source of new antibacterial substances that can be used in the prevention of caries, and Brazil is the richest country in terms of biodiversity. Objective: In this study, the disk diffusion method (DDM) was used to screen over 2,000 Brazilian Amazon plant extracts against Streptococcus mutans. Material and Methods: Seventeen active plant extracts were identified and fractionated. Extracts and their fractions, obtained by liquid-liquid partition, were tested in the DDM assay and in the microdilution broth assay (MBA) to determine their minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs). The extracts were also subjected to antioxidant analysis by thin layer chromatography. Results: EB271, obtained from Casearia spruceana, showed significant activity against the bacterium in the DDM assay (20.67±0.52 mm), as did EB1129, obtained from Psychotria sp. (Rubiaceae) (15.04±2.29 mm). EB1493, obtained from Ipomoea alba, was the only extract to show strong activity against Streptococcus mutans (0.08 mg/mL<MIC<0.16 mg/mL; MBC=0.16 mg/mL) in the MBA. Conclusions: The active extracts, discovered in the Amazon rain forest, show potential as sources of new antibacterial agents for use as chemical coadjuvants in prevention strategies to treat caries.